21 GROWTH, MOTOR, AND SOCIAL DEVELOPMENT IN BREAST- AND FORMULA-FED INFANTS OF METFORMIN-TREATED WOMEN WITH POLYCYSTIC OVARY SYNDROME. (1st March 2006) - Glueck, C. J.; Salehi, M.; Sieve, L.; Wang, P.
Abstract : Objectives: In a prospective, 6-month study of 61 breast- and 50 formula-fed infants born to 92 PCOS mothers, all of whom took metformin throughout pregnancy, our hypothesis was that metformin during lactation vs formula would have no adverse effects on infants' growth, motor-social development, and intercurrent illness. Study Design: Growth, motor-social development, and illness requiring a pediatrician visit were prospectively assessed in 61 nursing infants (21 male, 40 female) and 50 formula-fed infants (19 male, 31 female) born to 92 PCOS mothers taking a median of 2.55 g metformin/day throughout pregnancy and lactation. Results: Within gender, at 3 and 6 months of age, weight, height, and motor-social development did not differ ( p $ .06) between breast- and formula-fed infants. No infants had retardation of growth, motor, or social development. Intercurrent illnesses did not differ in 30% of breast- and 22% of formula-fed infants by 3 months ( p = .4) and in 46% and 34% by 6 months ( p = .2). Conclusions: Growth, motor-social development, and intercurrent illnesses in breast- and formula-fed infants from metformin-treated PCOS mothers did not differ; metformin during lactation appears to be safe and effective in the first 6 months of infancy.